PROSES PEMANFAATAN TABLET ANDROID SEBAGAI MEDIA PEMBELAJARAN PADA SISWA SEKOLAH DASAR - Nur Febyanti; Trian Pamungkan Alamsyah; M. Taufik (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article focuses on the teaching and learning process that uses android tablets as learning media and describes the impact of the process of using the android tablet as learning media. The research method used in this article is a qualitative research method. Datacollection technique used interviews, observation, and documentation techniques. In this online learning, the android tablet was used as a learning medium. The teaching and learning process began with greetings, attendance, materials, assignments and closings. Generally, the sequence of learning implementation was the same as usual, but it was finished online by using this android tablet media and other supporting applications like WhatsApp and YouTube. The material was delivered in various ways such as through learning videos, voice messages, and text messages. Utilizing android tablets in the process of this learning implementation has an impact on students' improvement skills in using android tablets for learning, even though it has not been able yet to increase students’ motivation while studying at home.